Continuity among stayers: Levels, predictors and meanings of place attachment in rural shrinking regions. (December 2022) - van der Star, Marieke E.; Hochstenbach, Cody
Abstract: In many countries, social and economic disparities between regions appear to be on the rise, with the increasing demand for urban living mirrored by the decline of more peripheral regions. Increasingly often, this concerns shrinking rural regions. This paper focuses on residents' place attachment in two such regions: Sogn og Fjordane in Norway and Noord Friesland in the Netherlands. We study levels, predictors and meanings of place attachment by drawing on both quantitative survey data and qualitative in-depth interviews. Our findings reveal generally high levels of place attachment in both regions, likely reflecting stability among rural stayers. Women, the employed, long-term residents and those speaking the local language report significantly higher levels of attachment in both regions. Our qualitative material underscores that individual biographies are actively shaped by the social, cultural and physical dimensions of place. Respondents construct images of living in a rural idyll where a sense of normalcy, familiarity and natural quality is maintained. We argue these findings help understand why residents stay put in the face of regional decline. Highlights: This paper studies residents' place attachment in two shrinking rural regions in Norway and the Netherlands. We draw on both survey data to assess levels and predictors and interview data to understand meanings of place attachment. Our findings reveal generally high levels of place attachment in both regions, reflecting stability among rural stayers. Respondents construct images of a rural idyll where a sense of normalcy, familiarity and natural quality is maintained.